Reparating Women’s Rights Violation Within Aceh Truth and Reconciliation Commission (TRC) - M.Yakub Aiyub Kadir; Firmanila Firmanila (Faculty of law Udayana University, 2020)
The establishment of Aceh TRC is based on the 2005 peace agreement between the Indonesian Government and the Free Aceh Movement (GAM), which then regulated under Act No. 11 year 2006 on Governing of Aceh, and was manifested through the Aceh Qanun No. 17 year 2013 on Aceh TRC. Three years later, the commissioner of Aceh TRC was chosen and inaugurated by Aceh House of Representative on July 2016. This paper investigates Aceh TRC and its progress in fulfilling the rights of women as the victim of Aceh’s conflict, challenges and some recommendation for better implementation of TRC. Using a normative and empirical research, this paper found that Aceh TRC is an institution to uncover the truth of the past human rights violations, to achieve reconciliation and to recommend a comprehensive reparation. Currently (May 2019), Aceh TRC is collecting data to achieve the first goal that is uncovering the truth, while the rights of women as victim in Aceh’s conflict is remain alienated. It is recommended that Aceh TRC should implement the urgent reparations as soon as possible considering the condition of the women’s victim and their rights, and also for the central and provincial government to be supportive in terms of financial and moral support.